Molecular characterization of Phytophthora cinnamomi, the cause of root rot in Cherimoya (Annona cherimola L.) on the central coast of Peru (Bioagro, 2025)
Cherimoya (Annona cherimola Mill.) is a plant that is cultivated mainly in the inter-Andean valleys of the Lima region, Peru, which present suitable conditions for its production. However, these conditions also favor the development of pathogens that cause the decline and death of cherimoya plants. The objective of the study was to molecularly identify the causal agent of cherimoya root rot. Cherimoya roots with mild and severe symptoms of root rot were collected from the valleys: Huanangui, San Antonio de Cumbe and Huaral, Lima. Seven Phytophthora isolates were obtained on PDA and V8 media with coralloid, petiolate mycelium, coenocytic hyphae with hyphal swellings, obpyriform sporangia, ovoid without papillae and globose chlamydospores. The cytochrome oxidase subunit II (Cox2) and elongation factor alpha 1 (EF1-α) regions were amplified using primers FM75, FM78, EF1AF and EF1AR. The sequences obtained showed a similarity of 99,22 to 99,87 % for Cox2 and 99,04 to 100 % with EF1-α for Phytophthora cinnamomi. The phylogenetic tree showed a topology consistent with the Phytophthora accessions. It is concluded that P. cinnamomi is the cause of root rot, this being the first report on the presence of this pathogen in custard apple plants in Peru.
Keywords: Cox2; EF1-α; Oomycete; soil pathogen; zoospore